THE IMPORTANCE OF DIDACTIC GAMES IN THE SPEECH DEVELOPMENT OF PRIMARY SCHOOL STUDENTS - Rustamova Davlatkhon Toyirjon qizi; Abdumajidova Guliza Ravshanjon qizi (The Conference Hub, 2025)
This thesis examines the importance of didactic games in the development of speech among primary school students. Didactic games, which combine learning and play, are a highly effective educational tool for enhancing students' vocabulary, pronunciation, and grammar. The study focuses on how these games foster cognitive skills, creativity, and social interactions, all of which contribute to speech development. Practical examples of didactic games and their application in the classroom are also explored. The thesis highlights the value of integrating didactic games into primary education to make learning more engaging, interactive, and beneficial for children's speech development.
Keywords: Didactic Games, Speech Development, Primary School Education, Vocabulary Enhancement, Pronunciation, Grammar Skills, Cognitive Development, Social Skills, Interactive Learning, Creative Play, Educational Tools, Classroom Application